Defense Method for Smart Grid GPS Spoofing Attack Based on BiLSTM and Self-attention Mechanism Generative Adversarial Network - Hui WU; Ziwei ZOU; Fengming XIAO; Jie LIU; Chenpeng MIN; Zhuoqun XIA (Zhongguo dianli)
Phasor measurement unit (PMU) plays a crucial role in smart grids, enabling precise synchronized acquisition of electric power data. Due to the use of the global positioning system (GPS) for time synchronization, the PMU is vulnerable to GPS spoofing attack (GSA), which impacts the normal data acquisition. The existing GSA defense methods have low restoration accuracy and require additional hardware costs. To address the aforementioned issues, this paper proposes a GSA defense method based on bidirectional long short-term memory (BiLSTM) network and self-attention mechanism generative adversarial network. Firstly, an improved WGAN-GP model is proposed to redesign the network architecture of the generator and discriminator, and the BiLSTM network and self-attention mechanism are incorporated into the generator and discriminator to enhance the model's generative performance and discriminative ability. Secondly, based on the proposed WGAN-GP model, a GSA defense model is constructed, which includes two crucial modules: an attack detection network and a data restoration network that are employed to detect the smart grid GSA and repair the compromised PMU measurement data, respectively. Finally, We simulated GSA attacks in the IEEE-39 bus system and validated the effectiveness of the proposed method on the corresponding dataset. The results show that compared to existing methods, the proposed approach outperforms in most performance indicators.